(3JMdjd GSS GdGbJUGOjGJ GdeGdjIs - (3ZGRj YHO GdQRGb(B, (3GdfbGTs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2003)
(3GdaUd GdChd (B: (3GdSjGSI GdeGdjI eDTQGJ dYedjI GdehGRfI (B: (3JWhQ GdSjGSI GdeGdjI hhXGFagG (B: (3Jchjf GdSjGSI GdeGdjI(B-(3GdaUd GdKGfj (B: (3GdJMdjd GdGbJUGOj ddeGdjI GdMchejI (B: (3GdJhGRf GdSjGSj (B: (3GdbGYOI GdVQjHjI(B-(3GdaUd GdKGdK (B: (3GdJMdjd GdGbJUGOj ddehGRfI (B: (3WHjYI GdBKGQ (B: (3eaghe GdYLR Ch GdaGFV (B: (3ehGRfI GdGSJNOGe GdJGe(B-(3GdaUd GdQGHY (B: (3CgOGa GdehGRfI heMOOGJ GdfabGJ GdYGeI(B-(3GdaUd GdNGeS (B: (3YedjI GdehGRfI hJMdjd GdcdaI(B-(3GdaGFOI(B-(3GdaUd GdSGOS (B: (3CfhGY GdVQGFH(B-(3GdaUd GdSGHY (B: (3JMdjd GdLhGfH GdJfXjejI ddehGRfGJ feGPL CfXeI deLehYGJ GdOhd(B-(3GdaUd GdKGef (B: (3GdCSdhH GdhXjaj dYedjI GdehGRfI JMdjd GdCHYGO GdJWHjbjI(B-(3GdaUd GdJGSY (B: (3JNWjW GdfabGJ hGdJfHD(B-(3GdaUd GdYGTQ (B: (3YLR GdehGRfI hGdOjf GdMchej(B-(3GdaUd GdMGOj YTQ (B: (3OQGSI JMdjdjI eQcRI dCHYGO GdSjGSI GdeGdjI aj GdfXQjI hGdJWHjb(B-(3GdaUd GdKGfj YTQ (B: (3OhQ GdeGdjI GdYGeI (B((3GdNRGfI(B) (3aj GdCShGb GdeGdjI hGdJehjd GdMchej GdaUd GdKGdK YTQ (B: (3JMOjO GdONd hfXQjI GdGSJbQGQ , GdaUd GdQGHY YTQ (B: (3GdCKGQ GdfGLeI Yf JWHjb SjGSI GdehGRfI GdeJeKdI aj hGbY GdVQjHI hCKGQ GdGfJGLs
(3HjHdjhZQGajG U(B.339s
Keywords: (3GbJUGOjGJ GdeGdjIs; (3GdeGdjI GdYGeIs; (3JMdjd GbJUGOjs